Assessing research methodologies used to evaluate inequalities in end-of-life cancer care research: a scoping review protocol. Issue 7 (20th July 2022) - Davis, Laura E; Webber, Colleen; Datta, Geetanjali D; Wiens, Allison; Harper, Sam; Hallet, Julie; Coburn, Natalie G; Konikoff, Lauren; Tanuseputro, Peter; Mahar, Alyson L
Abstract : Introduction: To provide equitable cancer care at the end of life, it is essential to first understand the evidence underpinning the existence of unequal cancer outcomes. Study design, measurement and analytical decisions made by researchers are a function of their social systems, academic training, values and biases, which influence both the findings and interpretation of whether inequalities or inequities exist. Methodological choices can lead to results with different implications for research and policy priorities, including where supplementary programmes and services are offered and for whom. The objective of this scoping review is to provide an overview of the methods, including study design, measures and statistical approaches, used in quantitative and qualitative observational studies of health equity in end-of-life cancer care, and to consider how these methods align with recommended approaches for studying health equity questions. Methods and analysis: This scoping review follows Arksey and O'Malley's expanded framework for scoping reviews. We will systematically search Medline, Embase, CINAHL and PsycINFO electronic databases for quantitative and qualitative studies that examined equity stratifiers in relation to end-of-life cancer care and/or outcomes published in English or French between 2010 and 2021. Two authors will independently review all titles, abstracts and full texts to determine which studies meet the inclusion criteria. Data from included full-text articles will be extracted into a data form that will be developed and piloted by the research team. Extracted information will be summarised quantitatively and qualitatively. Ethics and dissemination: No ethics approval is required for this scoping review. Results will be disseminated to researchers examining questions of health equity in cancer care through scientific publication and presentation at relevant conferences.